Augmentation of restless leg syndrome (Willis-Ekbom disease) during long-term dopaminergic treatment. Issue 7 (4th November 2015) - Garcia-Borreguero, Diego; Benitez, Arturo; Kohnen, Ralf; Allen, Richard
Abstract: Restless legs syndrome (RLS), also known as Willis-Ekbom disease (WED), is a common sensorimotor disorder that can generally be effectively managed in the primary care clinic. However, some treatment complications may arise. According to the recommendations of the International Restless Legs Syndrome Study Group, non-ergot dopamine-receptor agonists have over the past years been one of the first-line treatments for patients with RLS/WED requiring pharmacological therapy. Augmentation is the main complication of long-term dopaminergic treatment of RLS/WED and is defined as an overall worsening of symptoms beyond pretreatment levels in patients who experienced an initial positive therapeutic response. Once identified on the basis of its characteristic clinical features, augmentation requires careful management. In order to provide clinicians with a comprehensive understanding of this common treatment complication, this review discusses the clinical features of augmentation, and its differentiation from morning rebound, symptom fluctuations and natural disease progression. Reported incidences of augmentation in clinical trials of dopaminergic RLS/WED therapies are summarized. Finally, the hypothetical pathophysiology of augmentation and the current recommendations for management of patients with augmented RLS/WED symptoms are discussed.